Volatility spillover impact of world oil prices on leading Asian energy exporting and importing economies' stock returns. (1st December 2019) - Ashfaq, Saleha; Tang, Yong; Maqbool, Rashid
Abstract: Today Asia accounts for about 40% of the world oil trade and most of the trade is transpired within the region. This study presents an investigation of the volatility spillovers among leading Asian oil exporting countries and oil importing countries' stock exchanges and crude oil returns. The model selection from multivariant GARCH models include BEKK-GARCH, DCC-GARCH, ABEKK-GARCH and ADCC-GARCH estimation techniques which are applied using daily data from 1st September 2009 to August 31st, 2018 for the three oil exporting countries (Saudi Arabia, United Arab Emirates, Iraq) and four oil importing countries (China, Japan, India, South Korea) stock exchanges with spot crude oil. Further, these estimation results are used to analyze the optimal portfolio weights for oil-stock portfolios. The bidirectional spillover is accepted for the correlation of two oil exporting countries (Saudi Arabia, Iraq) and South Korean stock return with oil returns. the Overall the results of all the oil exporting and oil importing countries show a different level of significant correlation with oil but the influence of oil shock are more pronounced on oil exporting countries. We also present a graphical picture of the stock correlation with oil by employing DCC-GARCH model that shows great shock and volatility correlation in the period of the oil crisis of 2014–2016. According to optimal portfolio weights and hedge ratios, the oil assets are a useful instrument to minimize the portfolio risk in studied markets. The investors, however, should choose more stocks than oil assets to form an optimal portfolio in case of oil importing countries and equal ratio for the oil exporting countries.